EFFECT OF FEEDING BYPASS PROTEIN ON NUTRIENT UTILIZATION OF BARBARI KIDS - Singh, VP; Nayak, S; Baghel, RPS; Gupta, RS; Patil, AK; Khare, AK (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The objective of this study was to evaluate the effect of protected ground nut cake (GNC) on intake of nutrient and their utilization in growing goats. Fourteen goat kids (8.22 kg body weight and 3 month of age) were randomly divided into 2 groups of 07 kids each. In control group kids were given untreated GNC, while in treatment group they were fed concentrate mixed with formaldehyde treated GNC. Each kid was stall fed on concentrate and roughage, in the ratio of 50:50. Feeding trial was conducted for 90 days. Results of study indicated that the digestible crude protein intake (g per day, % body weight and per kg W 0.75) and total digestible nutrient intake (kg per day, % body weight and per kg W 0.75) in kids fed on bypass protein based ration were significantly (p
Keywords: Formaldehyde treated GNC; nutrient utilization; barbari kids